Glyphosate leaching through a sandy loam soil amended with cattle dung or rice husk ash: A laboratory column study - Garba, Jamilu; Samsuri, Abd Wahid; Ahmad Hamdani, Muhammad Saiful; Sadiq, Tariq Faruq; Nabayi, Abba (Malaysian Society of Soil Science, 2023)
This study investigated the influence of added organic materials on glyphosate mobility through sandy loam soil. An equivalent rate of 10 t ha-1 of either cattle dung or rice husk ash were mixed with the soil and inserted into leaching tubes Both soil mixture and controls were spiked with 20 mL of 200 mg L-1 glyphosate. This was followed by an addition 100 mL of stimulated rainfall and the leachate collected at time intervals (0,3,10,22,32,40,50 and 65 days) for glyphosate analysis. After 65 days, soils were cut into three, dried and determined for its glyphosate residual concentration. The data obtained was analysed and results revealed no significance difference (p > 0.05) in glyphosate concentration between the treatments, at time intervals (0,3,10,22,32,40,50 and 65 days) and from residual concentration in soil after leaching. Nonetheless, an increased concentration was obtained from both cattle dung (10) and rice husk (9) compared with control, indicating potential influence of these wastes on glyphosate mobility. The order of cumulative glyphosate concentration from post-leaching soils was as follows: control with 17.798 µg g-1 ; > soil + rice husk ash with 15.484 µg g-1 ; and > soil + cattle dung with 14.918 µg g-1 . Meanwhile, irrespective of the treatments applied, the concentration of glyphosate in the soil layers were of the following order: top layer with 17.020 µg g-1 ; > middle with 16.745 µg g-1 ; and > lower layer with 14.436 µg g-1 . The length of each layer was about 3.3 cm, suggesting low glyphosate mobility